HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG HIV/AIDS DENGAN STIGMA TERHADAP ODHA DI WILAYAH KERJA PUSKESMAS II DENPASAR SELATAN - Jeanne Valentina Natassa Bely Natassa Bely; Anak Agung Ayu yuliati Darmini (Jurnal Riset Kesehatan Nasional, 2020)
ABSTRACTBackground: HIV/AIDS is one of an infected disease. Until now days, there is not find an effective medicine or treatment to cure this diseases. The last six years, this disease shows an incretion rapidly either in the world or Indonesia. Often in the community people with HIV/AIDS has an alienated stigma. Purpose: To determine correlation  level of public knowledge about HIV / AIDS stigma to the people with HIV / AIDSMethod: The study design was descriftive correlational survey with crossectionamethod. Sample of the study was  100 respondents was taken by simple random sampling technique, Data was collected by a questionnaire and analyze by Spearman Rho statistical test with SPSS version 20. Result: The study Findings shows; 79% respondances classified into good categoriey, 85% classified into sufficient category poor. There is a significan correlation with negative direction between knowledge with stigma with the correlation value p= 0,000 (r = -0,543). Conclussion: Communit y Knowledge level has a closed correlation with stigma. More higer community knowledge level they will perform a low stigma. The community hope to find more information about HIV/AIDS in other to decriese stigma to the people with HIV/AIDS. Keywords: Knowledge, Public, HIV/AIDS, Stigma, ODHA.